Measurements of convective heat transfer around a single rod bundle for three gap spacing - Kayser, Fábio Matos (2020)
This work aims to evaluate the experimentally the convective heat transfer coefficient around a single rod bundleunder turbulent flow. The single rod bundle is part of a compound channel that is mainly characterized by their dimensionless numbers such as the Reynolds number, and the W/D-ratio. The gapwidth,δ,is the distance between the rod and the upper part of the channel. During the experimental campaign,the gap δwas changed its widthto 5, 10 and 15 mm, yielding a W/D= 1.05, 1.10 and 1.15, respectively. The dimension Wis the sum of the gapwidth, δ, and the cylinder’s diameter. The test section length was kept constant, 1800 mm. Special heated cell, controlled by a Minipa 3305 Power Supply, was designedin order to keep cell`s surface heated. The temperature on the cell`s surface was acquired through a set of special thermocouples on it. Afterwards, the wall temperature and the local minima in terms of convective heat transfer coefficient around the tube was determine and compared with those ones from the open literature. The J-data were found in fair agreement with those previously published. Moreover, the J-data location was not found in the narrow gap for the smallest W/D studied, but for locations away the gap (0°). When the gap becomes wider,the lowest local hreturned to the narrow gap position.Hot-wire probe was employed to measure the mean average and the turbulent velocity time traces at the gap vicinity. Coherent structures were seen to dominate the flow at such region, affecting the J-data locus.